Mongolia : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report, 2020)
This paper discusses Mongolia's Request for Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 pandemic has taken a large toll on economic activity in Mongolia, giving rise to urgent budget and balance of payments needs. The authorities have already taken several measures to limit the economic contraction and help the most vulnerable. Recent revisions to the budget allow for higher health and social spending as well as tax relief to affected households and businesses. In addition, the Bank of Mongolia has eased monetary and financial policies to help prevent a disorderly contraction in bank lending to the private sector. Emergency financing under the IMF's RFI will provide much needed support to respond to the urgent balance of payments and budgetary needs. Additional assistance from development partners will be required to support the authorities' efforts and close the financing gap. The authorities' commitment to high standards of transparency and governance in the management of financial assistance is welcome.